Feasibility Evaluation of an Android-based Nutrition App (Dietducate) Among Nutritionists Using the User Version of The Mobile Apps Rating Scale (uMARS) - Muhammad Iqbal; Elita Dwi Nurrahmawati; Husin Husin (Sekawan Institut, 2023)
Online nutrition consultations are one of the strategic measures utilized to address complex nutritional issues. The use of smartphones in Indonesia is on the rise, particularly smartphones with the Android operating system. Indonesia has entered the 4.0 Industrial Revolution, which involves the application of technology in a variety of fields, including the healthcare industry. One application of this technology is the creation of the android application